(untitled) (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Fever and sepsis after percutaneous nephrolithotomy (PCNL) secondary to urinary tract infection is a major determinant of overall post PCNL complications. This study aims to analyse infective complications after PCNL in relation to pre-operative urine culture status. Methods: A comparative analysis of post PCNL infective complications in pre-operative urine culture positive (Group A) and negative (Group B) was done for one year during June 2017 to May 2018 in department of urology, Bir Hospital, National Academy of Medical Sciences, Kathmandu, Nepal. Demographics, stone characteristics, mean operative time, post-operative hospital stay and post-operative complications as per Modified Clavien classification were compared between the two groups. Results: Out of total 136 PCNL patients, 51 were in Group A and 85 in Group B. Infective complications were significantly high, 28 (54.90%) in group A compared to 20 (23.53%) in group B, p=0.004. The most common isolate was Escherichia coli 19 (37.25%), sensitive to amikacin 37 (72.55%). The mean operation time, transfusion and hospital stay was not statically different in two groups. Morality occurred in 1 (1.96%) in group A. Conclusions: Infective complications were significantly high after PCNL in patients with preoperative positive urine culture, even when it was treated to sterile with sensitive antibiotics, compared to patients with preoperative negative urine culture.